A new high order iterative alternating decomposition explicit method to solve the heat conduction equation - Sahimi, M.S.; Subdararajan, E.; Subramaniam, M.; Hamid, N.A.A. (Universiti Kebangsaan Malaysia, 2000)
In this paper, a new iterative alternating decomposition explicit (lADE) scheme of order of accuracy similar to that of Sahimi et al. (1993) of the Mitchell-Fairweather variant is developed to solve the one-dimensional parabolic problem. It is based on the two-stage fractional splitting strategy suggested by D'Yakonov and our numerical experiments indicate that the method is more accurate than the recently developed Alternating Group Explicit (AGE) method of Peaceman-Rachford variant.